Digital Marketing Communication Strategy of Tourism Destination of Mandalika: A Semiotic Analysis - Farid Said; Achmad Daeng GS; Abdu Rahman; Muhammad Iqbal Djohan; Murdiani Sukarana (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2023)
The MotoGP event will be held in Indonesia located in Mandalika, Lombok. As Indonesia is hosting world-class event, it is an honor to be able to handle big event and earn achievement from that. With the aid of Instagram as social media, Mandalika Circuit actively promotes their campaign and information around MotoGP; thus, it is one of the key to further understand Indonesia diplomacy dynamics. Through @themandalikagp Instagram account using Saussure’s Semiotic Analysis, we can identify their sign and signifier then examine the relationship of it. The importance of Saussure’s Semiotic Analysis will expand new diplomatic perspective for Mandalika Circuit event and its potential.